Incest Without Punishment or “All Fur” from the First Edition of The Children’s and Household Tales (1812) by Brothers Grimm as a Unique Variant of the Type ATU 510b - Pieciul-Karmińska, Eliza (Porównania, 2023)
The paper offers an analysis of the tale “All Fur” (German: Allerleirauh) by Brothers Grimm in the version from the year 1812 in reference to the origins and editorial history of the Children’s and Household Tales (Kinder- und Hausmärchen). This early variant of “All Fur” contains a specific motif of incest and is, therefore, unique not only in comparison to the later editions of Grimms’ tales, but to other tales from type ATU 510b as well (for example, by Straparola, Basile or Perrault). The first edition of “All Fur” is often neglected in philological research, which is why the article discusses possible reasons for this surprising story about a happy marriage between father and daughter.